Le street art, outil de valorisation territoriale et touristique : l’exemple de la Galeria de Arte Urbana de Lisbonne - Alexandre Grondeau; Florence Pondaven (EchoGéo)
The lisboet's Galeria de Arte Urbana is a regional planning operation which consists in institutionalizing the practice of street art in the capital city of Portugal for territorial and touristic valorization purposes. This paper aims at showing how this operation was carried out alongside public policies in favor of culture and creativity, as well as and gentrification of the city’s historic center. We will study the functioning of the GAU, its organization, and its goals and will show how GAU modifies the evolution the local street art geography. We will analyze the territorial impacts of street art's institutionalization from social and economic points of view but also as regards urban marketing. Then we will question the limits for this operation and its criticisms notably as concerns the selection of works and authorized artists as well as private funding.